The Norwegian version of the nursing student mentors' competence instrument (MCI): A psychometric validation study - Silje Christin Wang Linnerud; Camilla Olaussen; Jaroslav Zlamal; Monica Evelyn Kvande; Kristine Haddeland; Andréa Aparecida Goncalves Nes (Elsevier, 2024)
Background: Nurse mentors require competence to mentor nursing students in clinical practice, including specific knowledge and skills. Evaluating mentor competence is crucial in developing and ensuring the high-quality mentoring of nursing students. The nursing student mentors' competence instrument is one of the few valid instruments for assessing the competence of nurses as mentors. Objectives: To translate the nursing student mentors' competence instrument into Norwegian and evaluate its psychometric properties. Design: The research employed a cross-sectional study design. Settings: Data were collected from nurse mentors at nursing homes, hospitals, home nursing care and mental health care units in Norway from 2021 to 2022. Participants: A total of 458 registered nurses with experience of mentoring nursing students participated in the study, of which data was used to conduct psychometric testing. Methods: The nursing student mentors' competence instrument was translated and evaluated in six steps: Forward translation, forward translation synthesis, backward translation, backward translation synthesis, cognitive debriefing and psychometric testing. The validity and reliability of the translated instrument were investigated using confirmatory factor analysis (CFA) and Cronbach's alpha. Results: The translated instrument showed acceptability. The CFA goodness-of-fit indices showed acceptable model fit (χ2/df = 2.547, SRMR = 0.051, CFI = 0.919, RMSEA = 0.058), and the Cronbach's alpha values for the instrument's subscales ranged from 0.77 to 0.95. Conclusions: The Norwegian version of the nursing student mentors' competence instrument shows potential as a useful instrument for assessing current and required competencies of nurse mentors in clinical practice in nursing education.